2018
DOI: 10.3389/fphar.2018.00360
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of Drug Response to Erlotinib in Chinese Advanced Non-small Cell Lung Cancer Patients

Abstract: The efficacy of erlotinib treatment for advanced non-small cell lung cancer (NSCLC) is due to its action as an epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI). Patients treated with erlotinib experience different drug responses. The effect of germline mutations on therapeutic responses and adverse drug responses (ADRs) to erlotinib in Chinese patients requires elucidation. Sixty Han Chinese advanced non-small cell lung cancer patients received erlotinib monotherapy and, for each participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…In the year of 2011, the expression of CYP4F2 was found by Falus et al to be a rapid elevation when children with respiratory disease to polarized light therapy [29]. In 2018, rs2074900 in CYP4F2 was found to be significantly related to therapeutic responses to erlotinib in sixty Han Chinese advanced non-small cell lung cancer patients received erlotinib monotherapy [16]. The above results indicated that CYP4F2 was involved in the pathogenesis of pulmonary disease and CYP4F2 variants played a vital role in the lung disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the year of 2011, the expression of CYP4F2 was found by Falus et al to be a rapid elevation when children with respiratory disease to polarized light therapy [29]. In 2018, rs2074900 in CYP4F2 was found to be significantly related to therapeutic responses to erlotinib in sixty Han Chinese advanced non-small cell lung cancer patients received erlotinib monotherapy [16]. The above results indicated that CYP4F2 was involved in the pathogenesis of pulmonary disease and CYP4F2 variants played a vital role in the lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…And Cytochrome P450 family 4 subfamily F member 2 (CYP4F2) encodes a member of the cytochrome P450 superfamily of enzymes involved in many metabolic pathways [14,15]. It is responsible for metabolizing arachidonic acid to 20-hydroxyeicosatetraenoic acid and involved in many reactions, such as drug metabolism [16], long-chain fatty acids metabolism [17], and synthesis of cholesterol, steroids and other lipids. Recently, Wang et al elucidated that the upregulated differentially expressed genes were significantly enriched in the arachidonic acid metabolism pathway, including CYP4F2, PTGDS and PLA2G16 by pathway enrichment analysis and pathway interactive network construction [18].…”
mentioning
confidence: 99%
“…The main focus has been on the variability in the emergence of skin rash. These studies have been conducted mainly using targeted approaches, either focusing on the erlotinib target (EGFR) or on erlotinib metabolizing and transporting enzymes, by studying single nucleotide polymorphisms (SNPs) in genes as well as sequencing of entire genes [58,60,65,[80][81][82][83][84][85][86][87][88].…”
Section: Pharmacogenetic Variability In Erlotinib Treatmentmentioning
confidence: 99%
“…The ABCB1 haplotype 1236TT-2677TT-3435TT has been associated with skin rash and with erlotinib plasma concentration [87]. Several metabolizing enzymes have been studied, for instance, have SNPs in CYP27B1 (rs8176345), CYP4F11 (rs1064796) and UGT3A1 (rs10045685) have been associated with skin rash and adverse drug reactions in erlotinib treated patients [81,83].…”
Section: Pharmacogenetic Variability In Erlotinib Treatmentmentioning
confidence: 99%
“…Wang and colleagues performed targeted sequencing to evaluate the link between EGFR and EGFR -linked pathway gene SNPs with EGFR -TKI response and ADRs in patients with advanced NSCLC [ 55 ]. They identified rs1042640 in UGT1A10 , rs1060463 and rs1064796 in CYP4F11 and rs2074900 in CYP4F2 as being associated with erlotinib treatment response, with improved an median PFS of 12.57 months compared to that of non-responders (median PFS 3.55 months) [ 55 ]. SNP rs1064796 in CYP4F11 and SNP rs10045685 in UGT3A1 were also linked to ADRs, with carriers of CYP4F11 -rs1064796-C and UGT3A1 -G showing an increased risk for skin rash or digestive track injury [ 55 ].…”
Section: Part I: Roles Of Common Genetic Variations In Cancer Pharmacmentioning
confidence: 99%